(untitled) (Architecture Image Studies, 2025)
This study presents a comparative analysis of three pioneering sustainable urban developments in the Gulf region: Msheireb in Qatar, Masdar City in the UAE, and NEOM in Saudi Arabia. Employing a qualitative evaluation framework based on the LEED assessment categories, the research explores how each city integrates environmental standards, technological innovation, and regional cultural identity. Msheireb emphasizes heritage preservation, dense urban fabric, and pedestrian-friendly design, utilizing traditional materials and passive cooling strategies. Masdar prioritizes a low-carbon footprint through renewable energy reliance, smart water management, and ecological compatibility, serving as a model for climate-adaptive urban planning. NEOM stands out with its futuristic vision, integrating AI, green technologies, and large-scale environmental protection, although its practical implementation remains under evaluation. The study underscores that regional context, cultural heritage, and technological maturity shape each city’s sustainability approach, highlighting the importance of tailored urban solutions. These insights contribute to understanding sustainable city planning in arid regions, emphasizing the need for balancing innovation with regional appropriateness to achieve long-term environmental and social resilience.